Sprachliche Beobachtungen zur Septuagintafassung von 2Kön (= 4Kön): das Griechisch der LXX und sein Verhältnis zum hellenistischen Griechisch - Winter, Franz (Protokolle zur Bibel, 2003)
This article deals with the character of the Greek of the LXX with special regard to 2Ki (= 4Ki LXX), whose German translation (with commentary) the author is preparing for the project "Die Griechische Bibel. Deutsch" (cf. http://www.uni-koblenz.de/~sept/index2.html). Two subjects are presented: l. The use of δε instead of και for Hebrew ו in translating ותאמר in 2Ki 4,2.13.16.23.26.28; 5,3 and the possible reasons for this change. 2. The importance of the greek documentary papyri of Egypt for the interpretation of the LXX illustrated on examples taken from 2Ki.